Ventricular function and dimensions in children with human immunodeficiency virus infection - Rahmat B. Kuswiyanto; Mulyadi M. Djer; Arwin A. P. Akib; Sudigdo Sastroasmoro (Indonesian Pediatric Society, 2011)
Background Prevalence of cardiac complications in children 'WithÂ human immunodeficiency virus (HIV) infection have increased,Â in association 'With the availability of antiretroviral (ARV) therapyÂ and the decrease of opportunistic infections. However, studies onÂ cardiac complications in HIV patients in the various HIV clinicalÂ and immunologic categories have been limited. Furthermore,Â cardiac complications in Indonesian HIVinfected children haveÂ never been reported.Objectives To detennine the prevalence of cardiac complicationsÂ in HIVinfected children and to compare ventricular function andÂ dimensions based on HIV clinical and immunologic categories.Â Methods A crossô€sectional study was done in the Department ofÂ Child Health, Cipto Mangunkusumo Hospital, Jakarta betweenÂ October and December 2009 on 7 4 HIVô€infected childrenÂ aged below 15 years. Children with severe chronic or acuteÂ systemic diseases were excluded. Investigations included physicalÂ examinations, 12ô€lead electrocardiography and echocardiographyto assess left ventricular dimension and ventricular function.Â Cardiac findings among children in different clinical andÂ immunological categories were compared.Results Five children showed left ventricular fractional shorteningÂ below 25% and 16 had right ventricular dysfunction. MeanÂ cardiac function and dimension were in the normal range. NoÂ differences in cardiac function and dimension, among the clinicalÂ HIV category groups (p>0.05) or immunologic suppression statusÂ groups (p>0.05) were observed.Conclusion In children 'With HIV infection, the prevalence of left ventricular dysfunction and right ventricular dysfunction was 7% andÂ 22%, respectively. No differences in cardiac function and dimensionÂ were found among the different HIV clinical and immunologicalÂ categories.